A comparative study of precision finishing of rebuild engine valve faces using micro-grinding and ECH - Harpreet Singh; Pramod Kumar Jain (Journal of Remanufacturing, 2015)
This paper presents a comparative analysis of process performance of micro-grinding and electrochemical honing, with the aim to achieve higher precision and surface quality of rebuild surfaces of the engine valve face. The discarded engine valve face was rebuilt using plasma transferred arc cladding technique and its surface finish was evaluated in terms of average roughness and maximum roughness value. The improvement in profile error and total run-out were used to evaluate the optimum processing time of micro-grinding and ECH. The sets of experiments for micro-grinding and ECH were conducted. The results reveal that the ECH process is one of the ideal choice for finishing of recovered surfaces. The surface morphology of the processed part is significantly improved resulting in glazed and uniform texture. Results show that the ECH can produce the workpiece surface 75 % efficient than the micro-grinding. A significant improvement of 23.37 % in the average surface roughness value was found after ECH as compared with the micro-grinding.
Keywords: 650; PTA; X40CrSiMo10-2 alloy steel; Micro-grinding; ECH; Product recovery; Engine valve; Surface quality